Implications of WTO DSB Panel Ruling on Imbalance of Power between WTO Member States - Luthfiah, Nyimas Sheila; Oppusunggu, Yu Un (Faculty of Law, Universitas Jambi, 2024)
Liberalization of trade, ease of market access and freer trade are one of the objectives from the establishment of World Trade Organization (WTO). Free and regulated trade can be achieved by having WTO as an international trade organization that regulates the trade-related of goods and services. International trade activities, however, have the tendency to generate disputes. WTO serves not only as an international trade organization but also as a choice of forum in settling trade disputes. Dispute settlement mechanism through WTO is conducted by using the Dispute Settlement Understanding (DSU) which contains the rules regulating the settlement procedures through WTO. WTO rulings are adopted by Dispute Settlement Body (DSB) and legally binding the disputing parties. Albeit the recommendations or rulings bind the parties, non-compliance on the rulings are susceptible to occur. More likely if the disputes are involving developing countries with the proclivity of having weak dispositions in international trade relations. Keywords: DSB; DSU; developing countries; retaliation; WTO